The Production of Food Commodities in Indonesia: Climate Change and Other Determinants - Hannoeriadi A., Ivan; Siregar, Hermanto; Asmara, Alla (Badan Penerbitan Fakultas Pertanian, Universitas Bengkulu, 2022)
One of the global problems that has a huge impact on the socio-economic conditions of the country, particulary on food security, is climate change. The El Nino Southern Oscillation (ENSO) is a climatic change phenomenon in Indonesia that has three phases: El Nino, La Nina, and Normal. Phenomenon has an impact on rainfall intensity, which bring another impact on the agricultural sector, food crops. This study examines the impact of climate change and other determinants on the production food commodities such as rice, corn, and soybean using the static panel data method. The cross section data focuses on the provinces on the island of Java which became the production center for rice, corn, and soybean, as well as four other provinces with the highest production for the three commodities mentioned. Time series data is used from 2009 to 2017. The results show that El Nino has a significant effect on decreasing rice and corn production and increasing soybean production. La Nina has a significant effect on increasing the production of the three commodities studied. Fertilizer subsidy has a significant effect on increasing the production of the three commodities studied meanwhile productivity significantly impact rice and corn productions.